2017
DOI: 10.1371/journal.pone.0170707
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological Factors Affecting Cortisol Variability in Human-Dog Dyads

Abstract: Stress responses within dyads are modulated by interactions such as mutual emotional support and conflict. We investigated dyadic psychobiological factors influencing intra-individual cortisol variability in response to different challenging situations by testing 132 owners and their dogs in a laboratory setting. Salivary cortisol was measured and questionnaires were used to assess owner and dog personality as well as owners' social attitudes towards the dog and towards other humans. We calculated the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 81 publications
3
29
0
2
Order By: Relevance
“…Owners scoring high on conscientiousness and openness had dogs with higher cortisol concentrations, and owners scoring high on neuroticism had dogs with lower concentrations. Interestingly, this is consistent with previous results on how owners' and dogs' personality traits influence short-term stress levels in dogs (168)(169)(170)(171). Thus, it seems that the owner has the greater influence on dog cortisol concentrations within the dyad and that dogs reflect the stress of their owners.…”
supporting
confidence: 91%
“…Owners scoring high on conscientiousness and openness had dogs with higher cortisol concentrations, and owners scoring high on neuroticism had dogs with lower concentrations. Interestingly, this is consistent with previous results on how owners' and dogs' personality traits influence short-term stress levels in dogs (168)(169)(170)(171). Thus, it seems that the owner has the greater influence on dog cortisol concentrations within the dyad and that dogs reflect the stress of their owners.…”
supporting
confidence: 91%
“… 42 This adds strength to our finding that personality may be associated with dog bite incidence. There also is evidence of an association between parent personality and child parenting style, 43 which appears to echo in links between owner personality and dog personality 44 and the nature of the dog–owner relationship. 45 These studies suggest that nervous/anxious owners may have nervous/anxious dogs, which may be another explanation for increased bite risk.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in cortisol concentrations in the owner was accompanied by an increase in the cortisol level in the dog. Schöberl et al [48] reported unequivocally that a greater impact on the variability of cortisol levels in human-dog pairs is exerted by the human. Kotrschal et al [49] found a significant impact of human personality (and thus susceptibility to stress factors) and behavior on the level of cortisol in dogs.…”
Section: Correlation Between Salivary Cortisol Level In the Handlers mentioning
confidence: 99%